Re-rooting/routing the Black Experience in Édouard Glissant’s Poetics: An “in-between” Perspective - Ly, Mamadou Moustapha (Dalhousie French Studies, 2022)
In his historical poetics, Édouard Glissant highlights the preponderant role played by the stripped migrant in his search for origins from Africa to the Caribbean. In so doing, he praises the latter’s endeavors throughout the adoption and adaptation to his new surroundings, the new world. In this article, the analysis is on the re-presentation of the past lived by the stripped migrant before, during, and after the moment of entanglement, when he started forming a rhizome-identity in comparison and contrast to the single-root identity perpetuated by the Békés. Such an approach brings to the fore the theoretical notion of detour developed by Glissant to defy and redefine the History or rather histories of the Caribbean archipelago that have been purposefully hidden by the “fictionneurs de l’Histoire” [History fiction writers], which makes him an atypical historian who gives a renewed version of the Afro-Caribbean tradition.